2015
DOI: 10.3758/s13414-015-0899-0
|View full text |Cite
|
Sign up to set email alerts
|

Working memory capacity and the scope and control of attention

Abstract: Complex span and visual arrays are two common measures of working memory capacity that are respectively treated as measures of attention control and storage capacity. A recent analysis of these tasks concluded that (1) complex span performance has a relatively stronger relationship to fluid intelligence and (2) this is due to the requirement that people engage control processes while performing this task. The present study examines the validity of these conclusions by examining two large data sets that include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
116
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(121 citation statements)
references
References 68 publications
5
116
0
Order By: Relevance
“…One possibility, for example, is that the effect is driven largely by performance variability in middle-and older-aged adults. O'Shea and Fieo (2014) found that fluid intelligence, which is highly correlated with WMC (Shipstead, Harrison, & Engle, 2015), predicted IB in older adults. However, this study did not directly test the IB-WMC association and used a relatively small sample, so the results may be affected by a few extreme scores.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility, for example, is that the effect is driven largely by performance variability in middle-and older-aged adults. O'Shea and Fieo (2014) found that fluid intelligence, which is highly correlated with WMC (Shipstead, Harrison, & Engle, 2015), predicted IB in older adults. However, this study did not directly test the IB-WMC association and used a relatively small sample, so the results may be affected by a few extreme scores.…”
Section: Discussionmentioning
confidence: 99%
“…Although this conclusion was predicted by Baddeley's (1986) classic model, it contrasts with perspectives that focus solely on domain-specific resources (e.g., Shah & Miyake, 1996;Süß, Oberauer, Wittmann, Wilhelm, & Schulze, 2002) or that assume that the properties of VSWM can be understood via either/or questions (e.g., slots OR resources; features OR objects; quality OR quantity; see Luck & Vogel, 2013). VSWM is multiply determined, and its properties are likely more complex than the unitary-resource proposals that are common in the literature (e.g., Luck & Vogel, 2013;Shah & Miyake, 1996;Shipstead et al, 2015).…”
Section: Discussionmentioning
confidence: 82%
“…That is, the factor labeled WM DG represents domain-general storage. Although we have no issue with interpreting WM DG as representing focal attention, we argue that focal attention largely arises from the ability to stabilize attention on relevant information (Shipstead et al, 2015).…”
Section: Domain-general Variance As Executive Attentionmentioning
confidence: 99%
See 2 more Smart Citations